Exploring concomitant concepts in the discussion on the circular economy: A bibliometric analysis of Web of Science, Scopus and Twitter - Mirzyńska, Anna; Kosch, Oskar; Schieg, Martin; Šuhajda, Karel; Szarucki, Marek (Technological and Economic Development of Economy, 2021)
A growing interest in the circular economy, which is seen in the intensification of public discourse, could lead to a danger of blurring the concept and introducing inefficiency in implementing circular economy-based solutions. This study explores the trend in concomitant or accompanying concepts of the discussion about the circular economy themes understanding regarding scientific publications (3,486 publications from Web of Science and Scopus) and popular (non-scientific) domain (represented by 106,504 tweets) in the years 2011–2018. By employing text mining, we calculated the Jaccard similarity index divided into years. The results reveal changes over time in themes accompanying the circular economy discussion and a trend of rising recognition of research-related keywords in general public discussion, with unweighted similarity reaching 39.44% in 2018. Our Twitter keyword research perspective indicates the need to consider the consumer’s role in the development of the circular economy – through keywords that are closely related to consumers’ daily activities.